A lightweight possession proof scheme for outsourced files in mobile cloud computing based on chameleon hash function. (1st January 2014) - Ren, Wei; Liu, Yuliang
In mobile cloud computing, mobile users usually upload working documents into cloud servers to facilitate pervasively accessing via mobile devices and ubiquitously cooperating among members in a mobile group. During periods between uploading and downloading files, the possession of original file at cloud servers needs to be proofed to mobile requesters upon file retrieval. Any mobile user or device can verify that cloud servers indeed possess the designated uploading file before any concrete downloading procedure. Moreover, such verification procedure should not induce much overhead in terms of computation, storage and communication for mobile devices. In this paper, we propose a family of schemes to address this problem without relying on any third party auditor or authority. They are named as randomly sampling check protocol, random commitment check protocol, and chameleon hash function-based protocol. All schemes are lightweight in terms of computation, storage and communication. The evaluation of security and performance is extensively analysed, justifying the applicability of the proposed schemes. We finally propose a general protocol (model) for remote possession proof to reveal the fundamental components in the protocols for dedicated security goal. Such general protocol unveils a uniform framework for possession proof protocols.